(3QSGdI aj UfY GdBdGJ GdMQHjIs - (3CMeO Hf CMeO GdfeSGefi GdQjas
(3ChdgG (B:s
(3MeOkG EdgfG SHMGfg dg GdMhd hGdbhI hGdEYGfI s
(3BNQgG (B:s
(3cedJ HMeO Gddg hMSf Yhfg hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B_ (3GdeZQH (B(1342(3O(B) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs